Hubungan Efikasi Diri dengan Hasil Belajar Bahasa Prancis di SMAN 91 Jakarta - Kartika Rizqi Fajrin; Ekowati, Sri Harini; Andika, Yunilis (Franconesia, 2024)
This research aims to determine whether there is a relationship between self-efficacy and the French language learning outcomes of 12th grade students at SMAN 91 Jakarta. This research uses a quantitative approach with correlational methods. Data was collected using questionnaires and the results of the Mid-Semester Assessment. To obtain a 58 samples, the population was reduced using the Simple Random Sampling technique. The indicators for measuring self-efficacy variables in this research refers to the theories of Bandura (2009), Yaqin (2019), Hodges (2018), and Rondier (2004). The validity test used the Product Moment correlation formula by Pearson. Reliability test used the Alpha Cronbach formula and showed a result of 0.952, which is included in the very high level of reliability. The normality test used the Kolmogorov-Smirnoov formula and showed a result of 0.200, which means the data is normally distributed. Then, a correlation test used the Product Moment formula from Pearson and obtained a result of 0.821. The test results show t count (10.778) > t table (1.673) or there is a significant relationship between self-efficacy and the French language learning outcomes of 12th grade students at SMAN 91 Jakarta. The coefficient of determination test results was 67%.